2018
DOI: 10.1016/j.stemcr.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

KLF4 Nuclear Export Requires ERK Activation and Initiates Exit from Naive Pluripotency

Abstract: SummaryCooperative action of a transcription factor complex containing OCT4, SOX2, NANOG, and KLF4 maintains the naive pluripotent state; however, less is known about the mechanisms that disrupt this complex, initiating exit from pluripotency. We show that, as embryonic stem cells (ESCs) exit pluripotency, KLF4 protein is exported from the nucleus causing rapid decline in Nanog and Klf4 transcription; as a result, KLF4 is the first pluripotency transcription factor removed from transcription-associated complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 33 publications
10
48
0
Order By: Relevance
“…Although KLF4 restores loss of stemness caused by deletion of Klf5 in murine ESCs , the fact that Klf4‐ null embryos can develop to term suggests either that KLF4 is dispensable for embryogenesis or there is a functional compensation by other KLF proteins . KLF4 and NANOG are among the first transcription factors to shut down their transcription when ESCs exit pluripotency, and nuclear export of KLF4 upon ERK activation is a critical first step to exit the naive pluripotent state and initiate ESC differentiation . In addition, KLF4 is required for expression of the telomerase reverse transcriptase (TERT) in human ESCs and binds β‐catenin through protein‐to‐protein interaction, allowing the recruitment of this dimer to the Tert promoter in murine ESCs .…”
Section: Regulation Of Self‐renewal By Klfs In Pluripotent Stem Cellsmentioning
confidence: 99%
“…Although KLF4 restores loss of stemness caused by deletion of Klf5 in murine ESCs , the fact that Klf4‐ null embryos can develop to term suggests either that KLF4 is dispensable for embryogenesis or there is a functional compensation by other KLF proteins . KLF4 and NANOG are among the first transcription factors to shut down their transcription when ESCs exit pluripotency, and nuclear export of KLF4 upon ERK activation is a critical first step to exit the naive pluripotent state and initiate ESC differentiation . In addition, KLF4 is required for expression of the telomerase reverse transcriptase (TERT) in human ESCs and binds β‐catenin through protein‐to‐protein interaction, allowing the recruitment of this dimer to the Tert promoter in murine ESCs .…”
Section: Regulation Of Self‐renewal By Klfs In Pluripotent Stem Cellsmentioning
confidence: 99%
“…For ES cells maintained in LIF/serum, KLF4 displayed low protein stability similar to the observed stability after removal of MEKi ( Figure S2). Previous studies demonstrated that these signaling pathways regulate gene transcription (Dhaliwal et al, 2018;Nichols and Smith, 2009;Theunissen et al, 2011;Zhang et al, 2010); therefore, we investigated the effect of individual signaling pathways on Klf4, Nanog, Oct4, Sox2, Klf2 and Klf5 transcription. We observed that the removal of MEKi alone or in combination with LIF/GSK3i for 12hr significantly reduces Klf4 and Nanog transcription, but Oct4, Sox2, Klf2 and Klf5 transcription remains unaffected ( Figure S3).…”
Section: Klf4 Protein Stability Is Regulated By Lif and Mapk Signalinmentioning
confidence: 99%
“…The MAPK pathway has been shown to have a role in KLF4 nuclear localization, ubiquitination and degradation (Dhaliwal et al, 2018;Kim et al, 2012;Kim et al, 2014). As early as 6hr after MEKi removal, KLF4 was observed to exit the nucleus, and cytoplasmic KLF4 undergoes proteosomal degradation (Dhaliwal et al, 2018). In addition, nuclear export was found to depend on the presence of both a KLF4 nuclear export signal (NES1 at 97-107) and the ERK phosphorylation site in KLF4 at S132 (Dhaliwal et al, 2018).…”
Section: Klf4 Protein Stability Is Regulated By Lif and Mapk Signalinmentioning
confidence: 99%
See 2 more Smart Citations